The language of the Gospel of Matthew - Engelbrecht, J. (1990)
This paper deals with the language of Matthew's Gospel language is seen as an aspect of the style of the Gospel. Because Matthew supposedly made use of sources which would have influenced his language, these possible sources are discussed. Next some characteristics of his language are pointed out with special focus on his vocabulary, after which some examples from the Gospel are discussed to illustrate to what extent his sources influenced his language usage.
Keywords: Vocabulary; Verbal agreement with Mark; Septuagintal feature; Sentence structure; Parallelisms; Hebraic; Grammatical peculiarities; Figures of speech; Chiastic ring compositions; Characteristic narrative style; Augustinian model; Aramaic influence; Parataxis; Parables; Sermon on the Mount